SIGNIFICANCE OF HOMESTEAD TECHNOLOGIES OF RAJENDRA AGRICULTURAL UNIVERSITY (RAU) AS A MEANS OF LIVELIHOODS FOR RURAL WOMEN OF BIHAR - R. VASANTHA, VEENITA KUMARI and (The Journal of Research, PJTSAU, 2019)
Women have been the deprived and under privileged members of the society. According to the census 2011 (Provisional Population Totals- India), it was estimated that 69.08 per cent of women population of India lived in rural areas. In case of Bihar State, it is 88.85 per cent. The overall literacy rate of female population in India is 65.46 per cent whereas, it is 46.40 per cent in case of Bihar (Census of India, 2011). Poor socio-economic conditions is the reason that they are not able to derive maximum benefits from training activities and developmental programs. This itself suggests the quantum of attention and measure that need to be taken by the State Government through its various functionaries at different levels, so that a majority of the female population of the state is not neglected. Data were collected in the year 2013 with the help of a structured interview schedule comprising of eighteen socio-personal, economic, communicational, psychological and situational variables to explicit the profile characteristics of rural women of Bihar and to assess the significance of selected nine homestead technologies of Rajendra Agricultural University (RAU) as a means of their livelihoods. The findings of the study showed that the respondents had medium level of overall personal, socio-economic, communicational, psychological and situational profile characteristics. Vermicompost, apiculture and mushroom production technologies were the most sought after enterprises as a means of livelihood for rural women of Bihar.